2020
DOI: 10.2334/josnusd.19-0320
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effects of repeated psychophysical stress on masseter muscle nociception in the nucleus raphe magnus of rats

Abstract: Psychophysical stress can cause neural changes that increase nociception in the orofacial region, particularly the masseter muscle (MM). The nucleus raphe magnus (NRM), which is located in the brain stem, serves the crucial role of regulating nociception through descending modulatory pain control. However, it remains unclear if neural activities in the NRM are affected under psychophysical stress conditions. This study conducted experiments to assess (1) whether neural activity, indicated by Fos expression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 44 publications
(67 reference statements)
2
12
0
Order By: Relevance
“…Dysfunction of descending pain control induces chronic pain in the deep craniofacial tissues [5], and functional changes in several areas of the brainstem, such as the rostral ventromedial medulla (RVM), are involved in the facilitation of nociception. Our recent report indicated that forced swim stress changes neural activity in the RVM associated with masseter muscle inputs [66]. It remains unclear whether a similar finding can be observed after repeated SDS conditioning, although SDS changes neural function in the RVM related to thermoregulation in the body [67].…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunction of descending pain control induces chronic pain in the deep craniofacial tissues [5], and functional changes in several areas of the brainstem, such as the rostral ventromedial medulla (RVM), are involved in the facilitation of nociception. Our recent report indicated that forced swim stress changes neural activity in the RVM associated with masseter muscle inputs [66]. It remains unclear whether a similar finding can be observed after repeated SDS conditioning, although SDS changes neural function in the RVM related to thermoregulation in the body [67].…”
Section: Discussionmentioning
confidence: 99%
“…Blockade of 5HT3 receptors in the Vc region inhibits enhanced TMJ-evoked neural activities in the rats after FS [ 190 ]. FS also increases neural activities in the nucleus raphe magnus evoked by masseter muscle stimulation with increases in the number of 5HT expressing neurons [ 191 ]. These findings indicate that FS causes dysfunction of descending pain controls associated with deep craniofacial nociception.…”
Section: Preclinical Models For Psychological Stress and Deep Craniofacial Pain ( Table 1 )mentioning
confidence: 99%
“…Accordingly, various pain models also displayed functional changes in 5‐HT mechanisms in the rostral ventromedial medulla [12], while the effects of psychological stress on 5‐HT mechanisms in the rostral ventromedial medulla have been inconsistent. Repeated forced swim stress and restraint stress decreased [14, 19] and increased [20] the number of 5‐HT positive cells, respectively, although both models displayed increased nociception. In accordance with those findings, increases and decreases in the 5‐HT content in the spinal dorsal horn [51] and rostral ventromedial medulla [52], respectively, were demonstrated in several neuropathic pain models.…”
Section: Discussionmentioning
confidence: 99%
“…The nucleus raphe magnus and lateral paragigantocellular reticular nucleus (LPGi), located within the rostral ventromedial medulla, constitute key elements of the descending pain controls [12,13] and are the sources of serotonergic (5-HT) projections to the C1/C2 region that regulates masseter muscle nociception. Many studies have revealed that psychological stress affected neuronal [14,15] and glial [16] activities in the rostral ventromedial medulla, while preventing neural activities in these areas inhibited stress-induced pain-like behaviors [17]. There is extensive evidence that 5-HT neurotransmission is sensitive to diverse stressors, and changes in 5-HT mechanisms in the brain could contribute to anxiogenic-like responses [18].…”
Section: Introductionmentioning
confidence: 99%